An evaluation of alternative measures of corporate tax rates - Plesko, George A. (Journal of Accounting and Economics, 2003)
This paper examines the ability of financial statement measures of average and marginal tax rates (MTR) to capture tax attributes utilizing firm-level tax and financial data. The results suggest commonly used average tax rate measures provide little insight about statutory tax burdens, and may introduce substantial bias into analyses of tax incidence. Financial statement-based proxies for MTR, particularly those based on simulation methods, are found to perform well in estimating current year tax rates. Both current year and present value MTR are found to be highly correlated with an easily constructed binary proxy of firms’ tax status.